Avaliação do programa de contratação de professor visitante: um olhar para a internacionalização da Universidade Federal da Paraíba - Silva, Vanusa Virgínia da (2023)
The education system in Brazil is still moving towards international insertion, but it needs policies that encourage the development of all Higher Education Institutions (HEIs) in view of the decrease in investments destined for education, with the support of development agencies being essential. In that regard, the Coordination for the Improvement of Higher Education Personnel (Capes) has a very relevant role in the evaluation of Postgraduate Programs (PPGs), for the training of human resources and for the internationalization of HEIs, since it launched in 2017 the Institutional Internationalization Program (Capes-PrInt). This way, the Federal University of Paraíba (UFPB) prepared an internationalization project to participate in Capes-PrInt, which contained some actions to be carried out in return for the program, among them, we emphasize that from 2017 onwards, the university proceeded with the training of Brazilian and foreign visiting professors with high knowledge to work in PPGs during a certain period. This work aimed to evaluate the hiring program for visiting professor as a UFPB internationalization tool. The research is classified in terms of its nature as basic, in terms of its objectives as descriptive, in terms of technical procedures as documentary, and in terms of approaching the problem as qualitative and quantitative. The techniques employed were document and content analysis. The context of the research comprised the hiring of visitors carried out by the UFPB in the period from 2017 to 2022. Data were collected through electronic sites and by requesting information to the integrated platform for ombudsman and access to information (Fala.BR). 103 visitors were hired, most of them male and Brazilians, in categories A and Senior, being 26 (25.24%) foreigners who formed the sample of this study. Of the 78 PPGs, 52 (66.67%) hired visitors. For analysis, we established categories and variables extracted from the lattes curricula about training and activities that indicate internationalization. We emphasize that 16 (80%) foreign visitors have a doctorate abroad and 20 (100%) have articles abroad. The results showed positive points regarding internationalization through visitors, as professors from other countries or with international experience who elaborated bibliographical productions abroad were hired, thus enabling the exchange of knowledge with students and permanent professors of the UFPB. However, we evidence weaknesses regarding the university not present information about the program in a centralized way, the activities developed are not registered in UFPB's integrated systems by all visitors to generate a bank of public data. In addition to the fact, they need to be more encouraged to participate in extension projects with international cooperation, to elaborate technical and artistic/cultural productions and to being advisors and members of work committees in educational institutions in other countries. Based on this information, we prepared a program report, identified some gaps, we made suggestions for the management of the UFPB and we created instructions for completing activity reports by visitors, especially internationalization, in order to systematize the evaluation process.